The Effect of Learning Model Two Stay Two Stray Containing Science Literacy on Learners Competencies at Junior High School 25 Padang - Yosi Safritry; Moralita Chatri; Relsas Yogica; Syamsurizal Syamsurizal (ATRIUM PENDIDIKAN BIOLOGI, 2019)
The research problems at SMPN 25 Padang namely learning activities carried out have little opportunity to be active in communicating fellow students, the learning interest of students is lacking, there is no learning model charged with scientific literacy, it is not yet known the effect of learning models containing literacy on students' learning competencies. The purpose of the study was to determine the effect of student learning competencies through the learning model of two stay two stray with scientific literacy at SMP 25 Padang. This type of research is experimental research with the design of the static group comparison design. The population of this study were all VII grade students of SMP 25 Padang. Sampling using a porposive sampling technique. Assessing the results of the two-class learning comparison, namely in class VII.4 as the experimental class, used the learning model of two stay two stray with scientific literacy, while class VII.2 as the control class. Based on the results of the students' competency knowledge research, the value of tcount was 3,92> ttable 1,67, the attitude competency was 81% for the experimental class, 72% for the control class and in the skills competency tcount 4,20> ttable 1,67. This shows that the hypothesis is accepted. The conclusion of the study is that the application of the learning model of two stay two stray with scientific literacy has a positive effect on the competency of knowledge, attitudes and skills ofjunior high school 25 PadangPadang.